The problem of the unemployment of people in Ukraine - Mischenko, M. I. (ТДАТУ, 2019)
The problem of unemployment in our country need much attention and it still plays an important and negative role in the Ukrainian society.
Keywords: the unemployment; increase in unemploym; the minimum wage